2016
DOI: 10.1038/ncomms11490
|View full text |Cite
|
Sign up to set email alerts
|

A 14 × 14 μm2 footprint polarization-encoded quantum controlled-NOT gate based on hybrid waveguide

Abstract: Photonic quantum information processing system has been widely used in communication, metrology and lithography. The recent emphasis on the miniaturized photonic platform is thus motivated by the urgent need for realizing large-scale information processing and computing. Although the integrated quantum logic gates and quantum algorithms based on path encoding have been successfully demonstrated, the technology for handling another commonly used polarization-encoded qubits has yet to be fully developed. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…These nanophotonic devices are important for emerging quantum technologies, such as photonic-based quantum computers [16,17] and quantum communication networks [18]. Following on from early work probing SPPs with quantum states of light, such as entangled photons [19], recent studies have demonstrated several key quantum applications, including quantum sensing and imaging [20][21][22][23][24], quantum spectroscopy [25], quantum logic gates [26], entanglement generation [27] and distillation [28], and quantum random number generation [29]. What is surprising is that all of these applications can be realized even in the presence of loss, which is always present in plasmonic systems as they are scaled down to confine light to smaller scales.…”
Section: Introductionmentioning
confidence: 99%
“…These nanophotonic devices are important for emerging quantum technologies, such as photonic-based quantum computers [16,17] and quantum communication networks [18]. Following on from early work probing SPPs with quantum states of light, such as entangled photons [19], recent studies have demonstrated several key quantum applications, including quantum sensing and imaging [20][21][22][23][24], quantum spectroscopy [25], quantum logic gates [26], entanglement generation [27] and distillation [28], and quantum random number generation [29]. What is surprising is that all of these applications can be realized even in the presence of loss, which is always present in plasmonic systems as they are scaled down to confine light to smaller scales.…”
Section: Introductionmentioning
confidence: 99%
“…The perfect RI material for LRSPPs in this study is LiNbO 3 , so steam will be absorbed by its surface and the RI will increase. When the RI changes significantly, LRSPPs cannot be excited, because the frequency is beyond the cut-off frequency of LRSPPs [21].…”
Section: Ri-matching Layer: Tio2mentioning
confidence: 97%
“…Surface plasmon polaritons (SPPs) can transmit or manipulate signals at the sub-micrometer or nanometer scale at optical frequencies because of their inherent properties, enabling SPPs to have many potential applications in integrated optics. Several SPP photonic devices have been reported, such as plasmonic demultiplexers [1], Airy beams [2], and polarization-encoded quantum-controlled NOT gates [3]. In addition, new theories, concepts, and applications of SPPs have emerged, including SPP holography [4], SPP crystals [5], nano-antennae [6], and plasmonic metamaterials [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By integrating the waveguides and controlling their coupling on a chip, basic optical elements [2] in bulk optics can be realized on-chip with high quality, such as beam splitter (BS), phase shifter and polarization beam splitter (PBS) [3,4] . Recently, quantum C-NOT gate, quantum walk and Boson sampling have been performed on a single chip, based on silica-on-silicon waveguides [5,6] , laser direct writing waveguides [7,8] and plasmonic waveguides [9,10] . While, there still remains challenges to integrate optical devices with good performance, and the errors due to experimental imperfection will be amplified when cascading many basic integrated devices together for future quantum computing, simulation and communication.…”
mentioning
confidence: 99%